A note on Gronwall type inequality for interval-valued functions - Román-Flores, Heriberto; Chalco-Cano, Yurilev; Silva, G. N. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In this paper, by using the concept of gH-differentiability and Kulisch-Miranker order on intervals, we show a differential Gronwall type lemma for inteval-valued functions defined on a real compact interval T. © 2013 IEEE.
Keywords: Interval-valued function